Impact of COVID-19 on liver transplantation in Hong Kong and Singapore: a modelling study - Tan, Eunice Xiang-Xuan (2023)
Background: Liver transplantation (LT) activities during the COVID-19 pandemic have been curtailed in many countries. The impact of various policies restricting LT on outcomes of potential LT candidates is unclear. Methods: We studied all patients on the nationwide LT waitlists in Hong Kong and Singapore between January 2016 and May 2020. We used continuous time Markov chains to model the effects of different scenarios and varying durations of disruption on LT candidates. Findings: With complete cessation of LT, the projected 1-year overall survival (OS) decreased by 3•6%, 10•51% and 19•21% for a 1-, 3- and 6-month disruption respectively versus no limitation to LT, while 2- year OS decreased by 4•1%, 12•55%, and 23•43% respectively. When only urgent (acute-on-chronic liver failure [ACLF] or acute liver failure) LT was allowed, the projected 1-year OS decreased by a similar proportion: 3•1%, 8•41% and 15•20% respectively. When deceased donor LT (DDLT) and urgent living donor LT (LDLT) were allowed, 1-year projected OS decreased by 1•2%, 5•1% and 8•85% for a 1-, 3- and 6-month disruption respectively. OS was similar when only DDLT was allowed. Complete cessation of LT activities for 3-months resulted in an increased projected incidence of ACLF and hepatocellular carcinoma (HCC) dropout at 1-year by 49•1% and 107•96% respectively. When only urgent LT was allowed, HCC dropout and ACLF incidence were comparable to the rates seen in the scenario of complete LT cessation. Interpretation: A short and wide-ranging disruption to LT results in better outcomes compared with a longer duration of partial restrictions.